Study of Architectural Ceramics of the Qal'a of Bani Hammad - Abla Brahimi; Messaoud Hamiane (Journal of Building Materials and Structures, 2018)
In order to define with precision, the physicochemical characteristics of the architectural ceramic exhumed from the Qal'a of Bani Hammad’s site (inscribed on the UNESCO’s World Heritage List in 1980), our study was conducted on a set of ceramics. The first analyses were focused on the color of the glazes, by optical absorption spectrophotometry (also called optical absorbance spectroscopy), on the texture by X-Ray diffraction, and on the elemental composition of the various constituent stages of these glazes and their terra cotta, by scanning electron microscopy and X-Ray fluorescence. Indeed, the study combining optical absorbance spectroscopy and X-Ray fluorescence enabled us to determine the origin of the monochromic green coloring of the glazes in some samples. This coloring can be attributed to the presence of the Cu2+ chemical element; but these glazes darkened due to the high iron content they contain. This could be explained by an intentional addition of iron, in tin-opacified leaded glazes, baked in an oxidizing atmosphere and put on a limestone-rich marlacious paste.